Left‐Hemispheric Microstructural Abnormalities in Children With High‐Functioning Autism Spectrum Disorder. Issue 1 (25th September 2014) - Peterson, Daniel; Mahajan, Rajneesh; Crocetti, Deana; Mejia, Amanda; Mostofsky, Stewart
<x xml:space="preserve">Abstract</x> Current theories of the neurobiological basis of autism spectrum disorder (ASD) posit an altered pattern of connectivity in large‐scale brain networks. Here we used diffusion tensor imaging to investigate the microstructural properties of the white matter (WM) that mediates interregional connectivity in 36 high‐functioning children with ASD (HF‐ASD) as compared with 37 controls. By employing an atlas‐based analysis using large deformation diffeometric morphic mapping registration, a widespread but left‐lateralized pattern of abnormalities was revealed. The mean diffusivity (MD) of water in the WM of HF‐ASD children was significantly elevated throughout the left hemisphere, particularly in the outer‐zone cortical WM. Across diagnostic groups, there was a significant effect of age on left‐hemisphere MD, with a similar reduction in MD during childhood in both typically developing and HF‐ASD children. The increased MD in children with HF‐ASD suggests hypomyelination and may reflect increased short‐range cortico‐cortical connections subsequent to early WM overgrowth. These findings also highlight left‐hemispheric connectivity as relevant to the pathophysiology of ASD and indicate that the spatial distribution of microstructural abnormalities in HF‐ASD is widespread and left‐lateralized. This altered left‐hemispheric connectivity may contribute to deficits in communication and praxis observed in ASD. Autism Res2015, 8: 61–72. © 2014 International Society for Autism Research, Wiley Periodicals, Inc.